The tumor microenvironment across four dimensions: assessing space and time in cancer biology - Larson, Christina R.; Mandloi, Ayushi; Acharyya, Satwik; Carstens, Julienne L. (Frontiers in Immunology, 2025)
The tumor microenvironment is heterogeneous, structurally complex, and continually evolving, making it difficult to fully capture. Common dissociative techniques thoroughly characterize the heterogeneity of cellular populations but lack structural context. The recent boom in spatial analyses has exponentially accelerated our understanding of the structural complexity of these cellular populations. However, to understand the dynamics of cancer pathogenesis, we must assess this heterogeneity across space and time. In this review, we provide an overview of current dissociative, spatial, and temporal analysis strategies in addition to existing and prospective spatiotemporal techniques to illustrate how understanding the tumor microenvironment, focusing on dynamic immune-cancer cell interactions, across four dimensions will advance cancer research and its diagnostic and therapeutic applications.